Effects of a blocked versus an alternated sequence of balance and plyometric training on physical performance in youth soccer players - Muehlbauer, T.; Wagner, V.; Brueckner, D.; Schedler, S.; Schwiertz, G.; Kiss, R.; Hagen, M. (BMC Sports Science, Medicine and Rehabilitation, 2019)
Background: The sequence of blocked balance training (BT) followed by blocked plyometric training (PT) showed greater improvements in physical performance than vice versa and is explained by a preconditioning effect of BT-related adaptations on subsequent adaptations induced by PT. However, it remains unclear whether beneficial effects can also be induced using alternating instead of blocked BT and PT exercise sequences. Thus, we examined the effects of a blocked versus an alternated sequence of BT and PT on physical performance in trained individuals. Methods: Twenty young soccer players (13 years) were randomly assigned to a blocked (n = 10) or an alternated (n = 10) intervention group. Both groups trained balance and plyometric exercises for six weeks (two sessions/week). The exercises were conducted in a blocked (three weeks of BT followed by three weeks of PT) or an alternated sequence (weekly change of BT and PT). Assessment of pre- and post-training performance included measures of balance, muscle power, speed, and agility. Results: Mainly significant main effects of Test (i.e., pre- to post-test improvements) were observed for the Y-balance test (p = 0.014, 1.3 = Cohen`s d = 1.81), the squat jump (p = 0.029, d = 1.36), the countermovement jump (p = 0.002, d = 2.21), the drop jump (p = 0.004, d = 1.96), the split times/total time over 15-m sprinting (p = 0.001, 2.02 = d = 3.08), and the figure-T agility run (p < 0.001, d = 3.80). Further, tendencies toward significant Test x Group interactions were found for several items of the Y-balance test and for SJ height in favor of the blocked BTPT group. Conclusions: Our results indicate that the combined training of balance and plyometric exercises is effective to improve proxies of physical performance in youth soccer players. In addition, there is a limited advantage in some parameters of balance and muscle power for the blocked as compared to the alternated sequence of BT and PT.